STATISTICAL ANALYSIS OF MARRIAGE AND DIVORCE IN THE RUSSIAN FEDERATION AND ITS REGIONS - L. Davletshina; E. Dolgikh (Вестник университета)
This one of the most important problems of the Russian Federation - marriage and divorce of the population article considered. The dynamics of these phenomena for the period from 2010 to 2016 is investigated; the characteristics of the average age of men and women entering into marriage are given. Special attention is paid to the assessment of regional differences in marriage and divorce of the population. The multidimensional classification of the subjects of the Russian Federation on the indicators affecting the marriage of the population is carried out, and regression models are constructed for the Russian Federation as a whole, as well as for the largest groups of regions.